2018
DOI: 10.1038/s41394-018-0094-3
|View full text |Cite|
|
Sign up to set email alerts
|

Severe chronic pain following spinal cord damage: a pragmatic perspective for prescribing opioids

Abstract: The controversial issue of prescribing opioids to people with spinal cord damage who have severe pain is discussed in this paper. The reasons for concern regarding the increase in opioid prescription over recent years are outlined, along with a summary of the major potential adverse outcomes associated with opioids, such as falls, respiratory suppression, adverse endocrine effects, cognitive impairment, and the potential for opioid abuse, addiction and death. Situations when opioids are more appropriate are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Previously, it has been shown that lncRNA SNHG4 can promote osteosarcoma growth via sponging miR-224-3p, which can predict a poor survival and recurrence [31]. In addition, SNHG4 can promote cervical cancer progression via regulating miR-206 and YWHAZ [32].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that lncRNA SNHG4 can promote osteosarcoma growth via sponging miR-224-3p, which can predict a poor survival and recurrence [31]. In addition, SNHG4 can promote cervical cancer progression via regulating miR-206 and YWHAZ [32].…”
Section: Discussionmentioning
confidence: 99%
“…In the final linked dataset, each opioid prescription included the following variables: unique study ID, sex (men, women), age Our primary outcome was receipt of at least 1 opioid prescription during the second or third year postinjury. The final dataset contained 13,196 prescription fills for all schedules II, III, and IV controlled substances reported in the PDMP for the 503 individuals during the study timeframe. Focusing only on the 269 individuals who had an opioid prescription filled in the second and third years after injury reduced it to 3386 opioid prescription fills.…”
Section: Prescription Outcomesmentioning
confidence: 99%
“…[8][9][10][11][12] However, the management of chronic pain with prescription opioids is controversial and has gained increased attention in recent years. 13,14 Although opioids are not recommended as a first-line therapy for pain after SCI (their use has been recommended only as a last resort), they are commonly prescribed and often at high dosages, resulting in an increased risk of adverse outcomes. 4,10,12 Several studies have highlighted the increased risk of misuse, 15,16 unintentional injuries (eg, falls and overdose), 17,18 and mortality [15][16][17][18][19][20][21][22] associated with prescription pain medication use after SCI.…”
mentioning
confidence: 99%
“…It can manifest as multiple forms of chronic pain in areas where skin sensation is lost below the injury plane (Dones and Levi, 2018). The incidence of NP in patients with SCI is increasing annually (Wayne, 2018). There are currently no curative therapies for SCI-associated NP, and clinical management is limited to symptomatic treatment.…”
Section: Introductionmentioning
confidence: 99%